An analysis of the human resource management and business strategy : a case study of the Philips (Thailand) Company Ltd. - Sivalogathasan, Vasthiyampillai; Sununta Siengthai; Swierczek, F.W.; Singha Chiamsiri (Bangkok : Asian Institute of Technology, 2002)
The aim of this study is to examine the existing I-IRM practices in the Philips Thailand Company Ltd. (Philips Semiconductors Thailand and Philips Electronics Thailand) and to investigate whether there is a relationship between HRM and Business Strategy. Links between the J-IRM strategy and Business strategy is taken as the conceptual framework of' the study. Primary data were gathered from questionnaire, Annual reports, journal and web sites of companies were explored to gather secondary data. Fifty managers responded to the questionnaire and Human Resource Managers of two divisions of the company were further interviewed. It was found that well-defined and properly communicated HRM policy that is aligned with the business strategy of the company worked towards the achievement of company goals. Many managers were found to be praiseworthy existing HRM policy and practices. Correlation between existing HRYI policy and business strategy was found to be very significant. It was further found that existing HRM policy had a significant association with higher performance.
A research study submitted in paitial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2002
Keywords: Personnel management -- Thailand -- Case studies; Business planning -- Thailand -- Case studies